2018
DOI: 10.31086/tjgeri.2018.55
|View full text |Cite
|
Sign up to set email alerts
|

Evalution of Geriatric Infections in Palliative Care Center

Abstract: Palliative care aims to improve quality of care by providing symptom control among geriatric patients; therefore, infection control is of utmost importance as complications increase symptom burden, thus decreasing quality of life. Materials and Method: Medical records of patients aged ≥65 years hospitalized at the palliative care center were retrospectively reviewed. Data on age, sex, diagnosis, comorbidities, length of stay, discharge status and cultures were collected. Results: Mean age of 305 patients was 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In the study by Yuruyen et al, the rate of patients discharged was 52%, the rate of referral to intensive care was 15% and the mortality rate was 33% [5]. Akdogan et al found in their study that mortality rate in the PC center of a tertiary care hospital was 43.0%, referral to intensive care unit was 24.3%, and the discharge rate was 32.8% [13]. Mortality rates and intensive care referral rates of the patients included in our study were found to be consistent with the findings in literature.…”
Section: Discussionmentioning
confidence: 98%
“…In the study by Yuruyen et al, the rate of patients discharged was 52%, the rate of referral to intensive care was 15% and the mortality rate was 33% [5]. Akdogan et al found in their study that mortality rate in the PC center of a tertiary care hospital was 43.0%, referral to intensive care unit was 24.3%, and the discharge rate was 32.8% [13]. Mortality rates and intensive care referral rates of the patients included in our study were found to be consistent with the findings in literature.…”
Section: Discussionmentioning
confidence: 98%